(untitled) (Global Journals of Research in Engineering, 2024)
This paper explores the challenges associated with limited battery capacity in drones and presents a comprehensive analysis of strategies to optimize energy harvesting and extend flight durations Various energy generation methods including piezoelectric and solar harvesting are discussed along with electrical circuit generation for wireless charging and communication-enabled energy delivery The interdisciplinary nature of drone technology is highlighted emphasizing the need for ongoing research in renewable energy models and innovative solutions like laser charging The paper concludes with recommendations for further exploration and refinement of these strategies to enhance the future of UAVs